Stefan Dečanski as a New Tobit - Polovina, Nataša M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Although it is considered part of the Deuterocanonical books of the Old Testament, the Book of Tobit has been highly popular among readers since the early Christian era. This popularity was certainly influenced by its exciting content and its moral character. In Serbian medieval literature, references to the Book of Tobit are rare, yet it is interesting that they appear in two texts, each linked to Stefan Dečanski in its own way. These texts are the charter of King Dušan for the Church of Saint Nicholas in Dobrušta and the Hagiography of Stefan Dušan by Gregory Tsamblak. Focusing particularly on Tsamblak’s Hagiography, in which Stefan Dečanski is referred to as the “new Tobit”, the paper examines the nature and function of biblical quotations and allusions to the Book of Tobit. Tobit is just one of the Old Testament figures with whom the author compares his hero (Stefan Dečanski is also compared to Job, Joseph, David, Joshua, and others). Since Tsamblak’s goal was to present Stefan Dečanski as a martyr, the most emphasis in the Hagiography is placed on the parallel with Job. This concept aligns with the image of Dečanski as the new Tobit, who, like Job, is a type of the righteous man whom God tests. The thematic affinity between the story of the Old Testament Tobit and the hagiography of the Serbian king is clear (piety, blindness, healing through a miracle). However, the shared motifs do not end there. Many of the ideas and motifs considered key to interpreting the Book of Tobit are also present in Tsamblak’s Hagiography of Stefan Dečanski: the motifs of exile, prayer, and almsgiving are important in characterizing Stefan Dečanski. Therefore, Tsamblac’s comparison of Dečanski with Tobit is seen as a „thematic key” that bridges the gap between literal and figurative meanings.
Keywords: Tsamblak; blindness; exile; almsgiving; martyr; Old Testament; thematic clue